Analysis of E-Learning System for Online Learning In Environmental Media Campus of UNP - Nofri Hendri; Novrianti Novrianti; Rusdinal Rusdinal; Nurhizrah Gistituati (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2020)
Application of the learning process in a campus using the conventional method of the longer lead the learning process is not effective. This raises problems in the campus environment how to create an interactive learning atmosphere so that it does not cause boredom towards students. The concept of E-Learning is a technology that can provide solutions to learning problems. The use of E-Learning can be accessed by utilizing internet technology through computers. The method discussed in thisconcept E-Learning consists of distance learning and blended learning. Distance learning is a model of distance learning where distance and time are not a problem in its operation, while blended learning is a learning model that combines conventional learning techniques with the use of technology for the distribution of learning such as the web.Keywords : analysis, e-learning, conventional, distance learning, blended learning